Resistance to Wear during Friction without Lubrication of Steel-Cast Iron Pairing with Nanocrystalline Structure-Reinforced Surface Layers - Ihor Hurey; Pavlo Maruschak; Andy Augousti; Alan Flowers; Volodymyr Gurey; Volodymyr Dzyura; Olegas Prentkovskis (Lubricants, 2023)
During the TDT of 41Cr4 steel specimens, a uniformly reinforced white layer with a nano-crystalline structure is formed in the surface layers. The wear resistance of sliding friction without the lubrication of a pair of steel 41Cr4—grey cast iron EN-GJL-200 (EN) under the face-to-face (“ring-ring”) scheme has been studied. It is revealed that when the sliding velocity changes from 0.25 m/s to 4 m/s and the unit load changes from 0.2 MPa to 1.0 MPa, a pair with a reinforced surface layer on 41Cr4 steel specimens and unreinforced specimens of EN-GJL-200 (EN) grey cast iron has a higher wear resistance than an unreinforced pair. The wear resistance increases for both reinforced and not reinforced specimens operating in a friction pair.